Investigation on Shear Capacity of Joints between Steel Reinforced Concrete Special-Shaped Column and Reinforced Concrete Beam - Xiang, Ping; Lin, Yipeng; Huang, Wei; Ding, Faxing; Ye, Bailong; Deng, Zhiheng (Frontiers in Materials, 2020)
Steel reinforced concrete (SRC) special-shaped column structures have all properties of steel reinforced structures and special-shaped column structures. The design of SRC special-shaped column joints is of great importance to ensure that this structure can be widely used in earthquake-prone areas. This research adopts a new joint design style, and a pseudo-static test is carried out on three joints (JD-1, JD-2, and JD-3) between the SRC special-shaped column and the RC beam, and one joint (JD-4) between the RC special-shaped column and concrete beam. The working mechanism of joints and the function of steel in the shear resistance mechanism are analyzed. Based on the results of experimental research, this article presents formulas on the cracking capacity and shear resistance capacity of these joints with theoretical and applicative purposes. Taking into account all these facts, the high resistance capacity and reliability of the joint design method are manifested. Some conclusions derived from this research can be used as a reference for engineering practice.